Medical-Legal Partnerships: Supporting the Legal Needs of Women in Their Perinatal Care [16F]. (May 2020) - Gutierrez, Griselda; Saleeby, Erin; Celaya, Anna; Clouse, Julia; Hoffman, Catherine; Kornberg, Jessie
Abstract : INTRODUCTION: Medical-legal partnership (MLP) aims to address the numerous social determinants of health. In July 2018 we added an MLP service for pregnant and postpartum women in an underserved safety net hospital in Los Angeles County. Here, we examine the prevalence of legal needs ascertained by self-administered legal needs assessments and the conversion rate of referrals to legal cases. METHODS: The MLP service was implemented as part of the continuum of clinical care. Referrals are tracked as part of case management. Review of self-administered screenings provided our referral screen-positive rates. Of those clients referred, a case conversion rate was calculated when legal cases were generated. RESULTS: Legal needs were identified in the following areas: family law (27%), employment (25%), housing (11%), and immigration (11%). A 72% screen positive rate (79 of 110) was found when clinic staff (provider, nursing, or social worker) directly referred to the MLP. Legal advice was often provided to those who screened positive (64%). Conversion rates were also high with 58% of those referred for formal legal action resulting in open cases (46 of 79 referred). CONCLUSION: Legal needs, such as assistance with employment law for pregnancy related disability accommodations, may have direct impacts on perinatal outcomes. Incorporating the MLP in resource-limited clinical settings can be achieved by including stakeholders in its development. The high conversion rate of referrals to cases illustrates the ability of the medical staff and patients to effectively identify legal needs and then partner with legal aid groups to address these concerns.